Investigating on nanofluid based thermal management system for 18650 lithium-ion batery module with fixed contact surface - Goo Wei Hong (2023)
Lithium-ion baterry is a type of rechargeable baterry that utilizes the flow of lithium ions during charging and discharging process. Lithium-oin batteries play important role in the application of automotive and consumer electronics products. However, large amaunt of heat is generated by electrochemical reaction during charging and discharging process.